The financial literacy gender gap: A question of nature or nurture? - Ute Filipiak; Yabibal M. Walle (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
This paper empirically investigates the role of nurture for the frequently reported differences in financial knowledge between women and men and uses a quasi-experimental framework comparing individuals who live in a matrilineal with those in a patriarchal environment in India. The results of our empirical analyses show that women, on average, are less likely to know about different financial instruments and practices than men. In contrast, no differences in financial knowledge between women and men exist in the matrilineal cultural environment. Matrilineal women are also more financially literate than women who live in patriarchal regions. Education, English language skills and the use of different information sources like TV and radio explain a large part of these differences in financial knowledge among women. Although considering a number of important variables, the results of a Blinder-Oaxaca decomposition show that a sizable portion of the differences in financial knowledge remains unexplained, what could be explained by nurture.
Keywords: O1; I3; Z1; 330; gender and financial literacy; matrilineal and patriarchal societies; Blinder-Oaxaca decomposition